75. High Rates of Virologic Suppression with DTG/3TC in Newly Diagnosed Adults with HIV-1 Infection and Baseline Viral Load >500, 000 c/mL: 48-Week Subgroup Analysis of the STAT Study. (4th December 2021) - Rolle, Charlotte-Paige M; Berhe, Mezgebe; Singh, Tulika; Ortiz, Roberto; Wurapa, Anson K; Ramgopal, Moti; Jayaweera, Dushyantha; Leone, Peter; Matthews, Jessica; Cupo, Michael; Underwood, Mark; Angelis, Kostas; et al.
Abstract: Background: The primary analysis of the STAT study demonstrated the feasibility, efficacy, and safety of using DTG/3TC as a first-line regimen in a test-and-treat setting through 24 weeks, with therapy adjustments for baseline resistance or hepatitis B virus (HBV) co-infection. Here we present secondary analyses through Week 48 of virologic outcomes in participants by baseline viral load (VL). Methods: STAT is a single-arm study of treatment-naive adults with HIV-1 infection who initiated DTG/3TC ≤ 14 days after HIV-1 diagnosis without availability of screening/baseline laboratory results. If baseline testing indicated DTG or 3TC resistance, HBV co-infection, or creatinine clearance < 30 mL/min/1.73 m 2, then antiretroviral therapy (ART) was potentially adjusted and participants remained on study. Efficacy analyses included proportion of participants with HIV-1 RNA < 50 c/mL regardless of ART regimen at Week 48, among all participants (ITT-E missing = failure analysis) and among participants with available HIV-1 RNA data at Week 48 (observed analysis). Results: Of 131 enrolled, DTG/3TC treatment was adjusted in 10 participants, and of those with available data (n=7), all (100%) achieved HIV-1 RNA < 50 c/mL at Week 48. At Week 48, 82% (107/131) of all participants (Figure 1) and 97% (107/110) of those with available data (Figure 2) achieved HIV-1 RNA < 50 c/mL. Of participants with baseline VL ≥ 500, 000 c/mL, 89% (17/19) achieved HIV-1 RNA < 50 c/mL at Week 48; the remaining 2 withdrew from study. Of participants with baseline VL ≥ 1, 000, 000 c/mL, 90% (9/10) achieved HIV-1 RNA < 50 c/mL at Week 48 (Table); the remaining participant withdrew consent. Of the 17 participants with baseline VL ≥ 500, 000 c/mL with available data through Week 48, 76% (13/17) achieved virologic suppression by Week 24. One participant with baseline VL ≥ 500, 000 c/mL switched from DTG/3TC before the Week 48 assessment. Of the 9 participants with baseline VL ≥ 1, 000, 000 c/mL with available data through Week 48, most participants (8/9; 89%) were suppressed by Week 24. Figure 1. Virologic outcomes at Week 48, overall and by baseline VL and CD4+ cell count: ITT-E missing = failure analysis. Figure 2. Virologic outcomes at Week 48, overall and by baseline VL and CD4+ cell count: observed analysis. Table. Viral Load by Study Visit Among Participants with Baseline HIV-1 RNA ≥1, 000, 000 c/mL Conclusion: These data provide evidence for the efficacy and feasibility of using DTG/3TC as a first-line regimen in a test-and-treat setting, including among participants with very high baseline VL. Disclosures: Charlotte-Paige M. Rolle, MD MPH, Gilead Sciences (Grant/Research Support, Scientific Research Study Investigator, Speaker's Bureau)Janssen Infectious Disease (Scientific Research Study Investigator, Advisor or Review Panel member)ViiV Healthcare (Grant/Research Support, Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau) Tulika Singh, MD MS AAHIVS, Gilead (Grant/Research Support, Advisor or Review Panel member)ViiV (Grant/Research Support, Advisor or Review Panel member, Speaker's Bureau) Moti Ramgopal, MD FIDSA, Abbvie (Scientific Research Study Investigator, Speaker's Bureau)Gilead (Consultant, Scientific Research Study Investigator, Speaker's Bureau)Janssen (Consultant, Scientific Research Study Investigator, Research Grant or Support, Speaker's Bureau)Merck (Consultant, Scientific Research Study Investigator)ViiV (Consultant, Scientific Research Study Investigator, Speaker's Bureau) Dushyantha Jayaweera, MD, mrcog(uk), face, Gilead (Research Grant or Support)Janssen (Research Grant or Support)viiv (Research Grant or Support) Peter Leone, MD, viiv healthcare (Employee) Jessica Matthews, BS, ViiV Healthcare (Employee) Michael Cupo, Ph.D., GlaxoSmithKline (Employee) Mark Underwood, PhD, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Kostas Angelis, PhD, GSK (Employee, Shareholder) Brian Wynne, MD, ViiV Healthcare (Employee, Shareholder, I have shares in GSK, the part owner of ViiV) Deanna Merrill, PharmD, MBA, AAHIVP, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Christopher T. Nguyen, MD, ViiV Healthcare (Employee) Jean A. van Wyk, MB, ChB, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Andrew Zolopa, MD, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee)